Calcium Nitrate Fertilization Effect on Anthracnose Caused by Colletotrichum Gloeosporioides Penz., Tuber Rot By Rhizopus Stolonifer Ehrenb. and Yield in Dioscorea Alata Variety Atoroku After Fallow - Otusanya, M. O. (European Journal of Applied Sciences, 2021)
Calcium nitrate soil amendment fertilization effects on anthracnose disease caused by Collettrichum gloeosporioides, tuber rot by Rhizopus stolonifer and yield were determined in Dioscorea alata variety Atoroku (a local variety from South West Nigeria). The field design was RCBD (randomized complete block design) with 3 treatments and 3 replicates. The 3 treatments were calcium at 0, 2 and 4 kg ha–1 from calcium nitrate (analar grade) applied at 3 MAP (months after planting). N in the experimental site was below the critical determined for optimum yam production in South West Nigeria, but Ca, Mg and K were above the critical. At 4 MAP, shoot number (mean, 3.68) was comparable/similar across treatments, but shoot length (3.43 m) was higher in the 2 kg ha–1 treatment than others. At 5 MAP the control and 2 kg ha–1 calcium fertilized plants had higher shoot number, a mean of 5, than the 4 kg ha–1 calcium fertilized plants, whereas shoot length had become similar in the treatments. Tubers were inoculated and incubated for two weeks with Rhizopus stolonifer, an economic yam storage pathogen in Nigeria, after the 5MAP and 6MAP harvests. There were no significant differences in weight loss or infection in the incubated tubers at 5MAP. Weight loss of 11.01% in the 2 kg ha_1 incubated calcium-fertilized tubers were significantly higher than in the control (3.20%) and the 4 kg ha_1 treatment (1.90%) at 6MAP. However infection was significantly lower in the 2 kg ha_1 (0.78%) and 4 kg ha_1 (0.86%) calcium-fertilized tubers than the control (2.25%) at 6MAP. Calcium nitrate at 2 kg ha_1 and 4 kg ha_1 soil amendment may be used in smallholder farmers plots to reduce infection in D. alata variety Atoroku tubers if the six months after planting is desired for income as is the practice for white guinea yam 6MAP milk harvest in Nigeria. Anthracnose severity scored at 8MAP was moderately susceptible in the 4 kg ha_1 treatment (3.17), control (2.83) and the 2 kg ha_1 treatment (2.75) and were not significantly different from one another. Reduction of anthracnose may be further determined with one or two foliar sprays in addition to the 3MAP calcium nitrate soil amendment, as well as leaf calcium analysis to ascertain the optimum concentration commensurate to anthracnose resistance. Shoot number per plant at 8MAP was in the range 2.07 to 2.54 with no significant differences among the three treatments. Tuber number per plant was also not significantly different and was 3.55, 4.27 and 3.18 in the 0, 2 and 4 kg ha_1 treatments. Plant weight above the mound of 4.78 kg and tuber weight of 5.35 kg in the 4 kg ha_1 treatment at 8MAP harvest was significantly higher than the control (3.25 kg and 3.55 kg respectively), and the 2 kg ha_1 treatment (3.05 kg and 3.25 kg respectively), whereas both were similar in the control and the 2 kg ha_1 treatment. The 8MAP yield of 3.55 kg, 3.25 kg and 5.35 kg in the 0, 2 and 4 kg ha_1 treatment is the equivalent of 35.5, tons ha_1, 32.5 tons ha_1 and 53.5 tons ha_1 and are higher than the expected 15 to 25 tons ha_1 with 400 kg (8 bags) NPK 15-15-15 (ICS-Nigeria) and also in the range of the estimated potential of 30 to 75 tons ha_1 (Zinsou, 1997; Diby et al., 2004). Calcium nitrate soil amendment at 4 kg ha_1 is recommended for increase in yield in Dioscorea alata variety Atoroku after fallow in South West Nigeria or areas of similar soils.